Stability of ascorbic acid in vegetables submitted to different methods of cooking - Daiuto, Érica R. [UNESP]; Pigoli, Daniela R. [UNESP]; Vieites, Rogério L. [UNESP]; Smith, Robert E. (My University, 2014)
The effect of different cooking methods on the ascorbic acid content of pumpkin, carrots, broccoli and cauliflower was determined. Cooking with steam and microwaves preserved ascorbic acid better than other methods. The unconventional parts of these vegetables (leaves, surface and stems) had the same or more ascorbic acid content than the conventional parts. Pumpkin and carrot surfaces (peels) had nearly identical ascorbic acid contents compared to the pulps of the fresh vegetables. The ascorbic acid content in broccoli stems was 31.2 mg/100 g and in both flowers and leaves it was 24.3 mg/100 g. Cauliflower leaves had the largest concentration of ascorbic acid, 44.3 mg/100g, compared to the flowers and stems, which had 26.5 and 21.1 mg/100 g, respectively. These patterns remained after cooking by different methods used in this study. In general, cooking in microwaves or steam reduced the ascorbic acid less than boiling. However, the uncooked (raw) vegetables had the most ascorbic acid.
Keywords: Broccoli; Carrots; Cauliflowers; Cooking; Domestic cooking; Immersion; Microwaves; Pressure; Processing; Pumpkin; Steam; Vitamin C